Gene Expression Patterns in Roots of Camelina sativa With Enhanced Salinity Tolerance Arising From Inoculation of Soil With Plant Growth Promoting Bacteria Producing 1-Aminocyclopropane-1-Carboxylate Deaminase or Expression the Corresponding acdS Gene - Heydarian, Zohreh; Gruber, Margaret; Glick, Bernard R.; Hegedus, Dwayne D. (Frontiers in Microbiology, 2018)
Camelina sativa treated with plant growth promoting bacteria (PGPB) producing 1-aminocyclopropane-1-carboxylate deaminase (acdS) or transgenic lines expressing acdS exhibit increased salinity tolerance. AcdS reduces the level of stress ethylene to below the point where it is inhibitory to plant growth. The study determined that several mechanisms appear to be responsible for the increased salinity tolerance and that the effect of acdS on gene expression patterns in C. sativa roots during salt stress is a function of how it is delivered. Growth in soil treated with the PGPB (Pseudomonas migulae 8R6) mostly affected ethylene- and abscisic acid-dependent signaling in a positive way, while expression of acdS in transgenic lines under the control of the broadly active CaMV 35S promoter or the root-specific rolD promoter affected auxin, jasmonic acid and brassinosteroid signaling and/biosynthesis. The expression of genes involved in minor carbohydrate metabolism were also up-regulated, mainly in roots of lines expressing acdS. Expression of acdS also affected the expression of genes involved in modulating the level of reactive oxygen species (ROS) to prevent cellular damage, while permitting ROS-dependent signal transduction. Though the root is not a photosynthetic tissue, acdS had a positive effect on the expression of genes involved in photosynthesis.